Cresyl diphenyl phosphate (a novel organophosphate ester) induces hepatic steatosis by directly binding to liver X receptor α: From molecule action to risk assessment - Xinya Liu; Lanchao Sun; Yongfeng Lin; Jingyue Du; Huizi Yang; Chuanhai Li (Environment International)
Cresyl diphenyl phosphate (CDP), a novel organophosphate ester (OPE), has been increasingly detected in various environmental and human samples. However, its toxicity, mechanisms, and health risks remain largely unknown. In this work, we investigated CDP-induced hepatic steatosis through Liver X Receptor α (LXRα) pathway across the molecular interactions, signaling pathways, cell functions, animal effects, and population risks, and compared them to triphenyl phosphate (TPHP) and tricresyl phosphate (TCRP). Receptor binding results showed that all three OPEs bound to LXRα directly in the order of TCRP > CDP > TPHP. Docking results suggested that the three aryl groups played an essential role in the binding of these chemicals to LXRα. They also activated LXRα-mediated lipogenesis pathway and promoted lipid accumulation in HepG2 cells. The intracellular concentration and LXRα-bound concentration of the chemicals in HepG2 cells followed a consistent order of CDP > TCRP > TPHP. In mice, exposure to CDP activated LXRα-mediated de novo lipogenesis pathway, leading to hepatic steatosis. Risk assessment results suggested that few populations (5.38 %) face a LXRα-mediated hepatic steatosis risk from CDP exposure. Collectively, our results demonstrate that CDP could bind to LXRα, activate the subsequent de novo lipogenesis pathway, inducing hepatic steatosis, and increasing adverse health risks.